2013
DOI: 10.1007/s12032-012-0420-8
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput screening of tumor metastatic-related differential glycoprotein in hepatocellular carcinoma by iTRAQ combines lectin-related techniques

Abstract: Glycoproteomics is an important aspect in the research of cancer biomarker discovery. The objective of our study is to screen the profile of serum glycoproteins in hepatocellular carcinoma (HCC) patients and to discover differentially expressed glycoproteins in HCC with or without metastasis. We collected serum from HCC patients and divided them into two groups (non-metastatic HCC group and metastatic HCC group) according to 2002 UICC TNM staging system. Wheat germ agglutinin (WGA) lectin was used to enrich th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 44 publications
0
28
0
Order By: Relevance
“…21 It is a circulating serine protease inhibitor or serpin and an acute-phase protein secreted in the liver. It is involved in the inhibition of apoptosis, or modulation of local and systemic inflammatory responses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…21 It is a circulating serine protease inhibitor or serpin and an acute-phase protein secreted in the liver. It is involved in the inhibition of apoptosis, or modulation of local and systemic inflammatory responses.…”
Section: Resultsmentioning
confidence: 99%
“…These two enrichment techniques have been successfully employed in many studies of glycoproteins associated with various cancer types including lung cancer, 1215 breast cancer, 1618 prostate cancer, 19,20 and hepatocellular carcinoma. 2123 …”
Section: Introductionmentioning
confidence: 99%
“…So far, several groups have reported the applying of iTRAQ based quantitative proteomics approach in the study of hepatic cancer, especially for the screening of diagnostic or prognostic protein biomarkers. He et al have reported the serum biomarker screening of AFP negative HBV related HCC through the iTRAQ based approach [35]; Ko et al have reported the iTRAQ based quantitative analysis of HCC cancer stem cell proteome [36]; Huang et al have reported the iTRAQ based serum biomarker screening of the HCC micro-vascular invasion [37]; Qin et al, Yu et al and Wang et al have reported the screening of metastatic related proteins of HCC through iTRAQ based approach [33,38,39]; the iTRAQ based quantitative study of proteome change during HBV infection has also been reported [40,41]. However, the application of iTRAQ labeling in studying the molecular mechanisms and screening for biomarkers associated with the early recurrence/metastasis of H-HCC has not yet been reported to our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…While the mechanism responsible for its complex hepatocarcinogenesis is still under investigation, rapid hepatocellular carcinoma tumor proliferation due to dysregulation of the cell-cycle proteins is clear. Herein, we have taken advantage of the rapid proliferating nature of tumor cells in general and the high levels of hAAT expression found in hepatocellular carcinoma (30)(31)(32) and generated an effective vector system whereby transgene expression is dependent on the activation of two endogenously regulated promoters, i.e., 4ÂApoE/hAAT liver-specific promoter and recombinant human cyclin A2. In the context of oncolytic HSV-1, the 4ÂApoE/hAAT liver-specific promoter has also been shown to drive the expression of complementary sequences of selected miRNAs exclusively in hepatocellular carcinoma (33).…”
Section: Discussionmentioning
confidence: 99%